KAJIAN PROSPEK PENGEMBANGAN USAHA BUDIDAYA KEPITING SOKA (SCYLLA SERRATA) DI WILAYAH PESISIR (STUDI KASUS DI KECAMATAN MEURAXA, KOTA BANDA ACEH) - Yuzan Wardhana (Jurnal Agrisep, 2016)
The production of soft-shelled crabs are not too significant to make this commodity becomes restricted goods on the market, and policy efforts have been tried to do by the Aceh government and private sector but has not been able to increase production output is greater. In the existing conditions is precisely the problem arises because of the lack of buyers soft-shelled crabs, but now with a growing demand, the production of soft-shelled crabs themselves to the city of Banda Aceh have not been able to meet the needs of the growing market. Generally, this research has the objective to: (1) Identifying the aspects of production in qualitative descriptive accordance with the conditions found during the research period lasts and market aspects to marketing on the cultivation of soft-shelled crabs and (2) Determine the development strategy that can be applied to the cultivation of crab E. shelled by using SWOT analysis.This research was conducted in Gampong Lamjabat and Cot Lamkuweuh, Meuraxa district, Banda Aceh. This study was conducted in May to October 2013. The method used in this research is descriptive and qualitative survey research methods. Population and sample in the study consisted of two soft-shelled crabs those farmers who are at two point locations. In this study, the analysis methods to be used, ie using E. SWOT analysis. The conclusion of this study is not simultaneously harvest, weather effects, and the addition of hormones to accelerate moulting. The strategy is a priority recommendation to implement a strategy S - T (strength - threat) is very supportive of the policy of increasing the cultivation of soft-shelled crabs significant by directing the power to overcome the threat in developing the cultivation of soft-shelled crabs in Gampong Lamjabat and Cot Lamkuweuh. However, other strategic priorities can also be used to support the strategy of S - T it.